WORK MOTIVATION MEDIATES THE INFLUENCE OF EDUCATIONAL LEVEL AND WORK EXPERIENCE ON EMPLOYEE PERFORMANCE AT KUALA CENAKU PUBLIC HEALTH CENTER OF INDRAGIRI HULU REGENCY - Triyono, Aris; Istiqhomah, Istiqhomah; Hartika, Dewi; Rahayu, Tri (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The reason why the author was interested in conducting this research was based on the results of observations and initial interviews that the author conducted with several employees of Kuala Cenaku Public Health Center. Initial results show that there are still several problems related to absenteeism, such as arriving late, not attending without explanation, and also fluctuations in the number of services and programs implemented each year at Kuala Cenaku Public Health Center. The author found indications that this was influenced by the level of education, work experience and also the motivation of the employees. The aim of this research is to determine the direct and indirect influence between the variables of education level and work experience which are mediated by motivation on employee performance. Sampling was carried out using the questionnaire distribution method with 62 samples as respondents. The analysis method used is quantitative, data analysis is carried out using path analysis. The research results show that there is a direct and significant influence between the variables of education level on performance, education level on motivation, work experience on performance, work experience on motivation, and motivation on performance. Meanwhile, the variable level of education on performance which is mediated by motivation and work experience on performance which is mediated by motivation shows that there is no influence between these variables.Keywords : Education Level, Work Experience, Motivation, Employee Performance.